Neighbourliness and community: a study of changing social relationship patterns in a Malay rice growing village - Emby, Zahid (Universiti Putra Malaysia Press, 2003)
Kampung Paya (a fictitious name) is a Malay rice growing village within the Muda Irrigation Scheme (MADA). The village was first studied by the author in 1975 employing the participant observation method. Additional data was collected through regular visits to the village, the last visit being in May 2002. Additional data was collected using the same method as previously employed in the 1975 research project which was observation, participation and formal and informal interviews. This is a study of the pattern of social relationships that has emerged in the village ever since its adoption of double-cropping of rice and the accompanying modern techniques of cultivation. The study found that the modern cultivation techniques employed by the villagers had reduced the need for the rice farmers to be at their work place (the rice fields) for long periods of time. This in turn reduced the quantity and quality of their social relationships at the work place. However, an increase in income had permitted them to spend more money in the village coffee shops and restaurants (food stalls) which had mushroomed in the last few years, thus turning these locations into "meeting centres" for the villagers, taking over this role not only from their work place but also from the mosque and their home. In recent years, a pattern has emerged showing that social visits to neighbours' homes were on the decline and that attendance at the mosque for the noonday, afternoon, evening and night time prayers has also declined. This means that these locations are no longer important foci for social relationships to occur. However, on the whole, the fabric of social relationship that is in existence at present, though different in form and quality from the pattern that existed in the past, is close-knitted enough to maintain neighbourliness and a semblance of community among the villagers.